Sustainable Development With Natural Gas: An Analysis - Dr. Roop Raj (Revista Electronica de Veterinaria, 2024)
Abstract: The role of natural gas in enriching and improving the quality of life on earth has assumed central and critical importance. All sustainable “development goals enunciated by the UNO to create an enduring equitable and progressive global economic order can be achieved if there is more and more shifting from others sources of energy to natural gas as a source of energy. Natural gas is a reliable, affordable, safe, clean and environment friendly source of energy. Our multiple problems related to gender equality, poor quality of education, social tension, health hazards unleashing of fatal diseases, economic disparity, catastrophic results in the wake of climate change, scarcity of potable water, toxicity of air to breathe, all these and many more issues can be satisfactorily resolved if significant transition from other sources of energy to natural gas as a resource of energy takes place. It is heartening that this kind of transition has already happened on a massive scale. The importance of the natural gas as a source of energy is being increasingly realized the world over. That is why the misuse of natural gas is considered a panacea to translate all SDOs into reality which will help mitigate all our socio-economic disorders” and tensions.